Central Precocious Puberty as a Complication of Congenital Adrenal Hyperplasia in a Boy: Case Report (Bangladesh Journal of Child Health, 2021)
Precocious puberty has intense influence on physical and psychosocial well-being of affected children and raises a lot of concerns as well as uncertainties in family.Here,we report a case of Central precocious puberty (CPP)superimposed on peripheral precocious puberty (PPP) due to congenital adrenal hyperplasia(CAH).Bangladesh J Child Health 2020; VOL 44 (3) :184-187